High-porosity silicon / carbon interpenetrating composite material, preparation method thereof and application of lithium ion battery negative electrode
A high-porosity silicon/carbon interpenetrating composite material addresses uniform distribution and cost issues in silicon-carbon electrodes by using a porous silicon inner layer and dense carbon outer layer, achieving reduced expansion and extended cycle life with efficient, low-cost production.
Patent Information
- Application Number
- CN202411379424.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
Existing silicon-carbon negative electrode materials for lithium-ion batteries face challenges in uniform distribution of silicon and carbon elements, inefficient pore introduction leading to stress concentration and particle breakage, and high production costs due to the use of hazardous chemicals like silane gas.
A high-porosity silicon/carbon interpenetrating composite material is developed with a porous silicon inner layer and dense carbon outer layer, achieving uniform pore distribution and stress relief through a silicon/carbon interpenetrating structure, prepared using a method that avoids hazardous gases and complex equipment.
The composite material reduces electrode expansion, enhances cycle life, and lowers production costs while maintaining high initial efficiency and safety, with a synergistic effect from uniform porosity and stress diffusion.
Smart Images

Figure CN119208572A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery materials, and specifically relates to a high-porosity silicon / carbon interpenetrating composite negative electrode material for lithium ion batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely used in portable devices, power storage, and electric vehicles. Silicon anodes are the most promising candidates to replace graphite anodes in the next generation of LIBs because of their ultra-high capacity of 3579 mA h / g and suitable equilibrium potential (370 mV Vs. Li + / Li), which can greatly increase the LIB energy density to >300 Wh / kg and improve safety. However, Si (battery discharge state) to Li 15 Si4 (battery charging state) will produce ~380% lattice expansion, which makes silicon particles prone to rupture / crushing and loss of activity during the charge and discharge cycle. At the same time, the continuous expansion / contraction process will lead to the instability of the particle solid electrolyte interface (SEI) film, and the continuous consumption of lithium will cause irreversible loss of capacity, and ultimately lead to battery life decay. Reducing the primary silicon particles to nanometer scale and using carbon materials to form a buffer skeleton to prepare secondary silicon-carbon particles can effectively relieve the stress of circulating silicon and extend the life of active materials.
[0003] However, there are still three major problems facing the practical application of silicon-carbon materials: First, it is difficult to evenly distribute the silicon and carbon elements in the material at the nanometer or submicron scale, so the material particles in the cycle are very likely to produce great stress and breakage at the silicon-dense places, resulting in the decay of the cycle capacity; second, it is difficult for carbon to completely absorb the expansion stress of silicon, so it is necessary to further reserve expansion space inside the particles, but the existing process of introducing pores into the particles is inefficient and energy-consuming, and the introduced pores are uneven and not small enough; third, the preparation of existing silicon-carbon negative electrode materials requires the use of expensive and hazardous chemical silane gas (vapor deposition of nanosilicon inside porous carbon), resulting in high one-time investment and process costs, which greatly limits the development and application of silicon-based negative electrode materials. Therefore, designing and developing new silicon-carbon negative electrode materials and preparing silicon-carbon composite materials with uniform high porosity have important practical value and are expected to achieve practical negative electrodes for lithium-ion batteries with high safety, long life, high initial efficiency and low expansion. Summary of the invention
[0004] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to provide a high-porosity silicon / carbon interpenetrating composite material and a preparation method thereof and the application of a lithium-ion battery negative electrode, so as to realize a lithium-ion battery silicon-carbon negative electrode with low expansion, high reversible capacity, high initial efficiency and long cycle life, while realizing efficient and low-cost batch preparation.
[0005] In the present application specification, the “ / ” in “high porosity silicon / carbon interpenetrating composite material” represents “silicon-carbon composite”.
[0006] The high-porosity silicon / carbon interpenetrating composite material described in the present invention is a silicon-carbon particle material composed of an inner layer of porous silicon and porous carbon, and an outer layer of dense carbon layer, wherein the inner layer of porous silicon and porous carbon penetrate each other; the mass content of silicon in the composite material is 30-60%, and the mass content of carbon is 40-70%, the interior of the silicon-carbon particles has a uniform and high-density pore distribution, and the particle porosity is 40%-70%.
[0007] The uniform dispersion of silicon phase and buffer matrix carbon phase in the material can effectively release stress concentration in the material particles and reduce particle lithiation stress and expansion rate. At the same time, during the preparation process, by adjusting the composition and mixing ratio of the polymer compound in the process of molecular-scale organic self-assembly, the particle porosity of the silicon-carbon material can be controlled to achieve uniform and high-density pore distribution inside the silicon-carbon particles, and the particle porosity can reach 40%~70%; at the same time, the dense carbon layer can reduce the specific surface area of the material to <15 m 2 / g. The uniform high porosity of the silicon-carbon particles can significantly improve the material cycle life and reduce electrode swelling; the dense carbon layer can reduce irreversible capacity loss and improve the first coulombic efficiency.
[0008] The method for preparing the high-porosity silicon / carbon interpenetrating composite material provided by the present invention comprises the following contents: (1) adding the porous silicon material to the solvent L1 to disperse the material to obtain a dispersion liquid S1, adding the polymer compound to the solvent L2 to disperse the material to obtain a mixed liquid S2, and adding S2 to S1 to disperse the material to obtain a precursor mixed liquid S3; (2) separating the precursor mixed liquid S3 from the liquid, and further drying and pulverizing the precursor to obtain the precursor solid powder S4; (3) adding the dense carbon source to the solvent L3 and mixing, adding the precursor solid powder S4 and mixing again to obtain a mixed solution S5, and performing solid-liquid separation on the precursor mixed solution S5 to obtain a precursor solid powder S6; (4) The precursor solid powder S6 is sintered to obtain a high-porosity silicon / carbon interpenetrating composite material.
[0009] In the above method, further, steps (1) to (4) are respectively as follows: (1) The surfactant and solvent L1 are dispersed in the solvent L1 at a mass ratio of 1:(50-5000), and porous silicon is added and dispersed again to prepare a dispersion liquid S1; the polymer compound is added to the solvent L2 at a mass ratio of 1:(5-30) to obtain a mixed liquid S2; S2 is slowly added to the dispersion liquid S1 and dispersed to obtain a precursor mixed liquid S3; wherein the mass ratio of porous silicon to the polymer compound is 1:(0.2-2).
[0010] (2) separating the precursor mixed liquid S3 from the liquid, and further drying and pulverizing the precursor to obtain the precursor solid powder S4; (3) adding the dense carbon source to the solvent L3 in a mass ratio of 1:(3-30) and mixing, and then adding the precursor solid powder S4 and mixing again to obtain a precursor mixed liquid S5, wherein the mass ratio of the precursor solid powder S4 to the dense carbon source is 1:(0.1-2); performing solid-liquid separation on the precursor mixed liquid S5 to obtain a precursor solid powder S6 in which the dense carbon source is coated on the surface of the particles; (4) The precursor solid powder S6 is sintered in an inert atmosphere at a temperature of 700-1200°C for 2-8 hours to decompose and carbonize the polymer compound and the dense carbon source to construct a particle structure with silicon / carbon interpenetrating inside and a dense carbon layer outside, thereby obtaining a high-porosity silicon / carbon interpenetrating composite material.
[0011] In the above method, further, the porosity of the porous silicon material described in step (1) is 50% to 90%, the pore size is 50 to 200 nm, and the initial size is 10 to 80 nm.
[0012] In the above method, further, the surfactant described in step (1) is one of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and polydiallyldimethylammonium chloride.
[0013] In the above method, further, the solvent L1 in step (1) is a mixed solution of one or more of methanol, ethanol, isopropanol and deionized water.
[0014] In the above method, further, the polymer compound described in step (1) includes but is not limited to phenolic resin, polyaniline, polyethylene glycol, polyvinyl alcohol, polyethylene oxide, polypropylene oxide, and one or more combinations of block copolymers composed of them (the aforementioned phenolic resin, polyaniline, polyethylene glycol, polyvinyl alcohol, polyethylene oxide, polypropylene oxide). When it is a plurality of combinations, the mixing ratio is not limited. The polymer compound preferably has a coking value of 40-70%, and the pore size of the carbon material formed after carbonization is 2-30 nm and the porosity is 30-60%. These characteristics will help to form uniform and appropriate pores in the particles to accommodate silicon expansion.
[0015] In the above method, further, the solvent L2 in step (1) is a mixed solution of one or more of methanol, ethanol, isopropanol, and deionized water.
[0016] In the above method, further, the dispersion method in step (1) is a combination of one or more of stirring and ultrasound, and the dispersion time is 0.1~2h.
[0017] In the above method, further, the solid-liquid separation method in step (2) is one or more combinations of precipitation centrifugation, negative pressure rotary evaporation, and spray granulation; the drying method is one or more combinations of vacuum drying, blast drying, stirring drying, and hot pressing drying; the pulverization method is one or more combinations of high-energy ball milling, planetary ball milling, stirring crushing, and air flow crushing. Preferably, the precipitation centrifugation in step (2) is one of the sedimentation methods such as pH adjustment sedimentation, flocculation sedimentation, and static sedimentation, and then centrifugation is used at a speed of 5000~15000rpm; the negative pressure rotary evaporation is carried out under the conditions of a vacuum degree of -0.05~-0.2 MPa and 40~150℃; the spray drying is carried out under the conditions of an inlet temperature of 110~150℃; and the drying temperature is 70~180℃.
[0018] In the above method, further, the dense carbon source in step (3) is at least one of needle coke, pitch coke, petroleum coke, etc., and the dense carbon source is characterized by: coking value> 70%. This feature can help reduce the pores generated on the particle surface during carbonization and decomposition, thereby forming a dense carbon layer and reducing the specific surface area.
[0019] In the above method, further, the solvent L3 in step (3) is one or a combination of deionized water, alcohol, isopropanol, n-hexane, toluene, No. 120 solvent oil, quinoline, kerosene; the mixing method is one or a combination of stirring, ultrasound, planetary ball milling, and the duration is 0.2 to 8 hours; In the above method, further, in step (3), the solid-liquid separation of the precursor mixed solution S5 is performed by vacuum rotary evaporation or spray granulation. Preferably, the vacuum rotary evaporation is performed at a vacuum degree of -0.05 to -0.2 MPa and a temperature of 40 to 150°C; the spray granulation is performed at an inlet temperature of 110 to 150°C.
[0020] In the above method, further, the inert atmosphere in step (4) is nitrogen, argon or a mixture of nitrogen and argon, and the sintering heating rate is 1-50°C / min.
[0021] The present invention also provides the use of the high-porosity silicon / carbon interpenetrating composite material as a negative electrode material for a lithium-ion secondary battery.
[0022] Furthermore, the application is to use the high-porosity silicon / carbon interpenetrating composite material alone as an active material, mix it with a binder and a conductive agent, and coat it on a copper foil as a negative electrode of a lithium-ion battery; or, mix it with graphite in a certain proportion as a mixed active material, and then mix it with a binder and a conductive agent and coat it on a copper foil as a negative electrode of a lithium-ion battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects: Compared with the prior art, the present invention has the following beneficial effects: 1. The method of the present invention constructs a silicon / carbon interpenetrating structure by filling a carbon source inside porous silicon, thereby achieving uniform dispersion of silicon in the base carbon, avoiding agglomeration of silicon primary particles to cause stress concentration inside secondary particles, and thus reducing electrode expansion.
[0024] 2. The method of the present invention can self-assemble in the pores of porous silicon to form a stable and orderly supramolecular structure by regulating and adjusting the composition and proportion of the polymer compound. After carbonization treatment, uniform high-density pores are formed inside the particles, thereby greatly buffering the lithium-inserted expansion of silicon. Combined with the closed-pore effect of the dense carbon source on the surface of the secondary particles, the specific surface area of the material is reduced, and the unity of high porosity and low specific surface area of silicon-carbon particles is achieved, thereby extending the battery cycle life while ensuring a high first coulomb efficiency.
[0025] 3. In the high-porosity silicon / carbon interpenetrating composite material prepared by the method of the present invention, the coexistence of the silicon / carbon interpenetrating structure and its internal high porosity can achieve uniform distribution of silicon, carbon and pores in the secondary particles, promote uniform stress diffusion, and the silicon / carbon interpenetrating structure is also conducive to a more uniform distribution of pores in the particles; on the other hand, the silicon / carbon interpenetrating structure mechanically supports each other, so that the stress during the lithium insertion reaction is dissipated to the pores, thereby significantly inhibiting the stress accumulation inside the secondary particles during the cycle. Therefore, the silicon / carbon interpenetrating structure and its internal high porosity have a significant synergistic effect, which further improves the battery cycle life under the condition of extremely low negative electrode thickness expansion rate.
[0026] 4. The method of the present invention starts from porous silicon raw materials, which have a wide source and low cost. It adopts dispersion, mixing, drying, sintering and other processes, avoids the use of high-value hazardous gases (silane) and complex high-temperature deposition equipment (fluidized bed, rotary kiln), has high production efficiency and good production process safety, and has significant advantages in preparation cost and scalability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the structure of high porosity silicon / carbon interpenetrating composite material; Figure 2This is a cross-sectional picture of the high-porosity silicon / carbon interpenetrating composite material 1 prepared in Example 1. Figure 2 a is a SEM cross-sectional image after argon ion milling. Figure 2 b and Figure 2 c is the distribution diagram of silicon and carbon elements corresponding to the cross-sectional diagram; Figure 2 d and Figure 2 e is the secondary electron image and backscattered electron image under the electron probe after argon ion milling. Figure 2 f and Figure 2 g is the distribution diagram of silicon and carbon elements corresponding to the cross-sectional diagram; Figure 3 1 is a charge-discharge curve of the electrode of the high-porosity silicon / carbon interpenetrating composite material 1 prepared in Example 1 at a current density of 500 mA / g; Figure 4 The electrode thickness change of the soft-pack battery of the high-porosity silicon / carbon interpenetrating composite material 1 mixed with graphite electrode, graphite electrode and silicon-oxygen material mixed with graphite electrode during the charge and discharge process prepared in Example 1; Figure 5 This is a SEM scanning electron microscope cross-sectional view of the high-porosity silicon / carbon interpenetrating composite material 2 prepared in Example 2 after argon ion milling; Figure 6 1 is the charge-discharge curve of the electrode of the high-porosity silicon / carbon interpenetrating composite material 2 prepared in Example 2 at a current density of 500 mA / g; Figure 7 This is a SEM scanning electron microscope cross-sectional view of the high-porosity silicon / carbon interpenetrating composite material 3 prepared in Example 3 after argon ion milling; Figure 8 3 is the charge-discharge curve of the electrode of the high-porosity silicon / carbon interpenetrating composite material 3 prepared in Example 3 at a current density of 500 mA / g; Fig. 9 The charge-discharge curve of the electrode of the silicon / carbon interpenetrating composite particle 1 prepared in Comparative Example 1 without introducing a dense carbon layer at a current density of 500 mA / g; Fig.10 1 is the charge and discharge curve of the electrode of the low-porosity silicon / carbon interpenetrating composite material 2 prepared in Comparative Example 2 at a current density of 500 mA / g. DETAILED DESCRIPTION
[0028] The present invention is further explained below in conjunction with specific examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above invention content.
[0029] In the following examples, the percentage concentrations of the ethanol aqueous solutions used are all volume concentrations.
[0030] Example 1 (1) The surfactant was added to a 10% volume ratio of alcohol and water at a mass ratio of 1:1000, and the mixture was stirred and ultrasonically applied for 0.1 h. The porous silicon with an initial size of 20-50 nm was added and the mixture was stirred and ultrasonically applied for 0.1 h to prepare a dispersion S1. Phenolic resin was added to the alcohol solvent as a polymer compound and stirred for 0.1 h to obtain a mixed solution S2. S2 was slowly added to S1 and stirred and ultrasonically applied for 0.1 h to obtain a precursor mixed solution S3 in which porous silicon was uniformly dispersed in the phenolic resin. The mass ratio of porous silicon to phenolic resin was 1:0.5.
[0031] (2) The precursor mixed liquid S3 is subjected to negative pressure rotary evaporation at 50°C and -0.08 MPa, vacuum dried at 120°C, and stirred and crushed to obtain a porous silicon / phenolic resin solid powder S4.
[0032] (3) The micropores of asphalt coke were used as a dense carbon source, mixed with toluene and quinoline in a mass ratio of 1:5:10 and ultrasonically stirred for 0.2 h, and then solid powder S4 was added and ultrasonically stirred for 0.2 h to obtain a mixed liquid S5, wherein the mass ratio of S4 to asphalt coke was 1:0.62. S5 was subjected to negative pressure rotary evaporation at 130°C and -0.08 Mpa to obtain a solid powder S6 with asphalt coke coated on the outer surface of the particles; (4) The solid powder S6 is continuously sintered in an Ar gas atmosphere at 1100°C in a tubular furnace to decompose and carbonize the phenolic resin and the pitch coke, thereby constructing a particle structure in which porous carbon and porous silicon penetrate each other internally and a dense carbon layer is formed on the outside, and the composite with the porous silicon is completed to obtain a high-porosity silicon / carbon interpenetrating composite material 1.
[0033] Through nitrogen adsorption / desorption test, the specific surface area of the high-porosity silicon / carbon interpenetrating composite material 1 was measured to be 5.2 m based on the BET adsorption model. 2 / g, proving that the obtained silicon-carbon material has a low specific surface area. After argon ion cross-section grinding of the material, the cross-section of the particles was observed using a SEM scanning electron microscope and an electron probe. Figure 2 As shown in the figure, silicon and carbon elements penetrate each other in the material particles, with certain pores distributed, while the particle surface is smooth and complete, with a dense carbon layer of ~1 μm thick. The material was tested by mercury intrusion and its skeleton true density was 0.96 g / cm 3 According to the formula: theoretical true density = volume fraction of silicon in silicon carbon * 2.33 + volume fraction of carbon in silicon carbon * 2.24, the theoretical true density of the silicon carbon material can be obtained to be 2.27 g / cm 3According to the formula: Porosity = 1-mercury intrusion true density / theoretical true density, the porosity is calculated to be 57.7%, indicating that the particle has more pores inside to alleviate volume expansion.
[0034] The prepared high-porosity silicon / carbon interpenetrating composite material 1 was used as the negative electrode to make a button battery with a lithium sheet as the counter electrode. The charge and discharge tests were carried out at a current density of 200 mA / g. Figure 3 As shown, its first discharge specific capacity is 1478 mA h / g, the first charge specific capacity is 1297 mA h / g, the first coulombic efficiency is 87.8%, and its capacity retention rate after 30 cycles at a current of 500 mA / g is 89%, indicating that the material has fewer side reactions during the lithium insertion process and has high reversibility.
[0035] The high-porosity silicon / carbon interpenetrating composite material 1 was further mixed with graphite in a ratio of 5:95 as a mixed active material and prepared into an electrode with a same-surface capacity of 4 mAh / cm 2 The NCM811 positive electrode was matched and assembled into a soft-pack battery, and the change of electrode thickness during charge and discharge was monitored. Under the same soft-pack assembly conditions, it was compared with graphite electrodes and commercial silicon-oxygen material-blended graphite electrodes with the same specific capacity. Figure 4 As shown. The electrode expansion of the high-porosity silicon / carbon interpenetrating composite material 1 mixed with graphite electrode during 5 cycles of charge and discharge (0.52, 1.78, 2.73, 3.08, 3.06 μm) is lower than that of the graphite electrode (1.5, 2.94, 3.33, 3.53, 3.91 μm) and the silicon-oxygen material mixed with graphite electrode (2.72, 3.75, 4.23, 4.36, 4.2 μm), which proves that the internal pores of the high-porosity silicon / carbon interpenetrating composite material can effectively alleviate the volume expansion during lithium insertion.
[0036] The above shows that by filling porous carbon on the porous silicon framework, constructing a silicon / carbon interpenetrating structure and sealing it with a dense carbon source, a porous silicon and porous carbon inner layer that penetrate each other and a closed dense carbon outer layer can be obtained. The uniformly dispersed silicon phase and buffer matrix phase can improve the problem of uneven element distribution and even uneven stress in the particles, effectively inhibit the side reactions and volume expansion of the material during the lithium insertion process, reduce electrode expansion and extend the battery cycle life.
[0037] Example 2 (1) The surfactant was added to an alcohol:water = 2:8 solvent at a mass ratio of 1:500, stirred and ultrasonicated for 0.2 h, porous silicon with an initial size of 50-100 nm was added and stirred and ultrasonicated for 0.2 h to prepare a dispersion S1; phenolic resin and polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer were added to the alcohol solvent as a polymer composite and stirred for 0.2 h to obtain a mixed solution S2; S2 was slowly added to S1 and stirred and ultrasonicated for 0.2 h to obtain a precursor mixed solution S3 in which porous silicon was uniformly dispersed in the phenolic resin; wherein the added mass ratio was porous silicon: phenolic resin: polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer = 1:0.5:0.5.
[0038] (2) The pH of the precursor mixture S3 was adjusted to < 6.5 to allow it to precipitate, and the mixture was centrifuged at 10,000 rpm, dried under vacuum at 120°C, and crushed by high-energy ball milling to obtain a porous silicon / phenolic resin / polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer solid powder S4.
[0039] (3) Pitch coke was added as a dense carbon source to a mixed solvent of deionized water and isopropanol in a mass ratio of 1:4.9:0.5, ball milled for 8 hours, and then solid powder S4 was added and ball milled for 1 hour to obtain a mixed solution S5, in which the mass ratio of S4 to pitch coke was 1:0.46. S5 was spray dried at an inlet temperature of 130°C to obtain a solid powder S6 with pitch coke coated on the outer surface of the particles; (at least the ratio of pitch to S4 should be clear) (4) The solid powder S6 is continuously sintered in an Ar gas atmosphere at 900°C in a tubular furnace to decompose and carbonize the phenolic resin and asphalt coke to construct a particle structure with silicon / carbon interpenetrating inside and a dense carbon layer outside, completing the composite with porous silicon to obtain a high-porosity silicon / carbon interpenetrating composite material 2.
[0040] Through nitrogen adsorption / desorption test, the specific surface area of high-porosity silicon / carbon interpenetrating composite material 2 was measured to be 12.8 m based on the BET adsorption model. 2 / g, proving that the obtained silicon-carbon material has a low specific surface area. After argon ion cross-section grinding of the material, the cross section of the particles was observed using a SEM scanning electron microscope, such as Figure 5 As shown in the figure, the porous carbon formed by the polymer compound inside the material particles runs through the three-dimensional continuous porous silicon, while the particle surface is smooth and complete, with a dense carbon layer of ~1 μm thick. The material was tested by mercury injection and its skeleton true density was 0.86 g / cm 3 , and the theoretical true density of the material at this silicon-carbon content is 2.27 g / cm 3 , it can be calculated that its porosity is 62.1%. The true density and porosity are defined the same as in Example 1, indicating that the particles have abundant pores inside to alleviate volume expansion.
[0041] The obtained high-porosity silicon / carbon interpenetrating composite material 2 was used as the negative electrode to make a button battery with a lithium sheet as the counter electrode. The charge and discharge test was carried out at a current density of 200 mA / g. Figure 6 As shown, its first discharge specific capacity is 1708 mAh / g, the first charge specific capacity is 1469 mAh / g, the first coulombic efficiency is 86.0%, and its capacity retention rate after 30 cycles at a current of 500 mA / g is 92%, indicating that the material has fewer side reactions during the lithium insertion process and has high reversibility.
[0042] The above shows that by adjusting the combination of various polymer complexes (such as phenolic resin and polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer) and utilizing their organic self-assembly behavior, a higher density and uniform pore distribution can be achieved inside the silicon / carbon interpenetrating composite particles, thereby effectively inhibiting the volume expansion of the material and extending the service life of the particles; at the same time, the closed carbon layer can reduce the side reactions of the material during the lithium insertion process, achieving higher cycle retention without sacrificing too much first coulomb efficiency.
[0043] Example 3 (1) The surfactant was added to a 10% alcohol-water solvent in a mass ratio of 1:1000, and the mixture was stirred and ultrasonically applied for 0.1 h. The porous silicon with an initial size of 20-50 nm was added and the mixture was stirred and ultrasonically applied for another 0.1 h to prepare a dispersion S1. Phenolic resin and polyvinyl alcohol were added to the alcohol solvent as a polymer compound and stirred for 0.1 h to obtain a mixed solution S2. S2 was slowly added to S1 and stirred and ultrasonically applied for 0.1 h to obtain a precursor mixed solution S3 in which porous silicon was uniformly dispersed in the phenolic resin. The mass ratio of the added porous silicon: phenolic resin: polyvinyl alcohol was 1:0.5:0.5.
[0044] (2) The precursor mixed liquid S3 is subjected to negative pressure rotary evaporation at 50°C and -0.08 MPa, vacuum dried at 120°C, and stirred and crushed to obtain a porous silicon / phenolic resin solid powder S4.
[0045] (3) The micropores of asphalt coke were used as a dense carbon source, mixed with toluene and quinoline in a mass ratio of 1:5:10 and ultrasonically stirred for 0.2 h, and then solid powder S4 was added and ultrasonically stirred for 0.2 h to obtain a mixed liquid S5, wherein the mass ratio of S4 to asphalt coke was 1:0.46. S5 was subjected to negative pressure rotary evaporation at 130°C and -0.08 Mpa to obtain a solid powder S6 with asphalt coke coated on the outer surface of the particles; (4) The solid powder S6 is continuously sintered in an Ar gas atmosphere at 1100°C in a tubular furnace to decompose the phenolic resin to construct pores within the particles and to coke the asphalt outside the particles to close the internal pores, thereby completing the composite with porous silicon to obtain a high-porosity silicon / carbon interpenetrating composite material 3.
[0046] Through nitrogen adsorption / desorption test, the specific surface area of high-porosity silicon / carbon interpenetrating composite material 3 was measured to be 14.9 m 2 / g, which proves that the obtained silicon-carbon material has a moderate specific surface area. After the material is subjected to argon ion cross-section grinding, the cross section of the particles is observed using a SEM scanning electron microscope, such as Figure 7 As shown in the figure, the material particles are composed of high-density porous carbon formed by polymer composites, which runs through the three-dimensional continuous porous silicon, while the particle surface is smooth and complete, with a dense carbon layer of ~1 μm thick. The material was tested by mercury intrusion and its skeleton true density was 0.74 g / cm 3 , and the theoretical true density of the material at this silicon-carbon content is 2.27 g / cm 3 , it can be calculated that its porosity is 67.4%. The true density and porosity are defined the same as in Example 1, indicating that the particles have abundant pores inside to alleviate volume expansion.
[0047] The high-porosity silicon / carbon interpenetrating composite material 3 was used as the negative electrode to make a button battery with a lithium sheet as the counter electrode. The charge and discharge tests were carried out at a current density of 200 mA / g. Figure 8 As shown, its first discharge specific capacity is 1320 mA h / g, the first charge specific capacity is 1547 mA h / g, the first coulombic efficiency is 85.4%, and its capacity retention rate after 30 cycles at a current of 500 mA / g is 91%, indicating that the material has fewer side reactions during the lithium insertion process and has high reversibility.
[0048] The above results combined with Experimental Example 2 show that by adjusting the type and proportion of the polymer compound, the pore density and size of the silicon / carbon interpenetrating composite particles can be controlled, thereby changing the pore distribution characteristics inside the particles.
[0049] Comparative Example 1 (Silicon / carbon interpenetrating composite material without introduction of dense carbon layer) (1) The surfactant was added to a 10% alcohol-water solvent in a mass ratio of 1:1000, and the mixture was stirred and ultrasonically applied for 0.1 h. The porous silicon with an initial size of 20-50 nm was added and the mixture was stirred and ultrasonically applied for 0.1 h to prepare a dispersion S1. Phenolic resin was added to the alcohol solvent as a polymer composite and stirred for 0.1 h to obtain a mixed solution S2. S2 was slowly added to S1 and stirred and ultrasonically applied for 0.1 h to obtain a precursor mixed solution S3 in which porous silicon was uniformly dispersed in the phenolic resin. The mass ratio of porous silicon to phenolic resin was 1:0.5.
[0050] (2) The precursor mixed liquid S3 is subjected to negative pressure rotary evaporation at 50°C and -0.08 MPa, vacuum dried at 120°C, and stirred and crushed to obtain a porous silicon / phenolic resin solid powder S4.
[0051] (3) The solid powder S4 was not coated with any dense carbon source, but was continuously sintered in an Ar gas atmosphere in a tubular furnace at 1100°C to decompose the phenolic resin to construct pores within the particles, thereby obtaining a high-porosity and high-ratio comparative sample 1.
[0052] Through nitrogen adsorption / desorption test, the specific surface area of high porosity and high specific surface area comparison sample 1 was measured based on the BET adsorption model to be 20.34 m 2 / g, proving that the obtained silicon-carbon material has a high specific surface area. Charge and discharge tests were carried out at a current density of 200 mA / g. Fig. 9 As shown, its first discharge specific capacity is 1642 mA h / g, the first charge specific capacity is 1221 mA h / g, and the first coulombic efficiency is 74.3%.
[0053] The above shows that since the silicon / carbon interpenetrating composite particle comparison sample 1 without introducing a dense carbon layer did not introduce a dense carbon source to form a dense carbon layer during the synthesis process, although it has high porosity, its high specific surface area will greatly reduce the first coulomb efficiency of the material, making it difficult to put into practical use.
[0054] Comparative Example 2 (low-porosity silicon / carbon non-penetrating composite material) (1) Nanosilicon with an initial size of 50-100 nm and pitch coke as a dense carbon source were ball milled at a ratio of 1:0.93 for 2 h.
[0055] (2) The ball-milled powder was continuously sintered in an Ar gas atmosphere at 900°C in a tubular furnace to carbonize the pitch on the outside of the particles to close the internal pores, thereby obtaining a non-penetrating comparative sample 2.
[0056] Through nitrogen adsorption / desorption test, the specific surface area of low-porosity comparison sample 2 was measured to be 11.6 m based on the BET adsorption model. 2 / g, which proves that the obtained silicon-carbon material has a low specific surface area. The charge and discharge tests were carried out at a current density of 200 mA / g. Fig.10 As shown in the figure, its first discharge specific capacity is 2106 mA h / g, and its first charge specific capacity is 1893 mA h / g. Although the first coulombic efficiency is 89.9%, its capacity retention rate after 30 cycles at a current of 500 mA / g is only 19%.
[0057] The above shows that at the same silicon-carbon content, since the low-porosity silicon / carbon do not penetrate each other, the comparison sample 2 did not compound the porous silicon with the polymer compound to form a porous and silicon / carbon mutually penetrating core during the synthesis process. Although its low specific surface area can achieve a high first coulomb efficiency, there is no polymer compound to regulate the porosity of the particles, and the expansion stress during the lithiation process cannot be relieved, resulting in a significant reduction in the cycle life and difficulty in practical application.
Claims
1. A high porosity silicon / carbon interpenetrating composite material, characterized in that: The high-porosity silicon / carbon interpenetrating composite material described in the present invention is a silicon-carbon particle material composed of an inner layer of porous silicon and porous carbon, and an outer layer of dense carbon layer, wherein the inner layer of porous silicon and porous carbon penetrate each other; the mass content of silicon in the composite material is 30-60%, and the mass content of carbon is 40-70%, the interior of the silicon-carbon particles has a uniform and high-density pore distribution, and the particle porosity is 40%-70%.
2. The method for preparing the high-porosity silicon / carbon interpenetrating composite material according to claim 1, characterized in that: Includes the following: (1) The surfactant and solvent L1 are dispersed in the solvent L1 at a mass ratio of 1:(50-5000), and porous silicon is added and dispersed again to prepare a dispersion liquid S1; the polymer compound is added to the solvent L2 at a mass ratio of 1:(5-30) to obtain a mixed liquid S2; S2 is slowly added to the dispersion liquid S1 and dispersed to obtain a precursor mixed liquid S3; wherein the mass ratio of porous silicon to the polymer compound is 1:(0.2-2); (2) separating the precursor mixed liquid S3 from the liquid, and further drying and pulverizing the precursor to obtain the precursor solid powder S4; (3) adding the dense carbon source to the solvent L3 in a mass ratio of 1:(3-30) and mixing, and then adding the precursor solid powder S4 and mixing again to obtain a precursor mixed liquid S5, wherein the mass ratio of the precursor solid powder S4 to the dense carbon source is 1:(0.1-2); performing solid-liquid separation on the precursor mixed liquid S5 to obtain a precursor solid powder S6 in which the dense carbon source is coated on the surface of the particles; (4) The precursor solid powder S6 is sintered in an inert atmosphere at a temperature of 700-1200°C for 2-8 hours to obtain a high-porosity silicon / carbon interpenetrating composite material.
3. The method according to claim 1, characterized in that: The porous silicon material described in step (1) has a porosity of 50% to 90%, a pore size of 50 to 200 nm, and an initial size of 10 to 80 nm; the surfactant described in step (1) is one of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and polydiallyldimethylammonium chloride.
4. The method according to claim 1, characterized in that: The polymer compound described in step (1) includes but is not limited to at least one of phenolic resin, polyaniline, polyethylene glycol, polyvinyl alcohol, polyethylene oxide, polypropylene oxide, and block copolymers thereof.
5. The method according to claim 1, characterized in that: The solvent L1 described in step (1) is a mixed solution of one or more of methanol, ethanol, isopropanol, and deionized water; the solvent L2 described in step (1) is a mixed solution of one or more of methanol, ethanol, isopropanol, and deionized water; the dispersion method described in step (1) is a combination of one or more of stirring and ultrasound, and the dispersion time is 0.1~2h.
6. The method according to claim 1, characterized in that: The solid-liquid separation method in step (2) is one or more combinations of sedimentation centrifugation, negative pressure rotary evaporation, and spray granulation; the drying method in step (2) is one or more combinations of vacuum drying, blast drying, stirring drying, and hot pressing drying; the pulverization method in step (2) is one or more combinations of high-energy ball milling, planetary ball milling, stirring crushing, and air flow crushing.
7. The method according to claim 1, characterized in that: The dense carbon source in step (3) is at least one of needle coke, asphalt coke, petroleum coke, etc., and the coking value of the dense carbon source is >70%; the solvent L3 in step (3) is one or a combination of deionized water, alcohol, isopropanol, n-hexane, toluene, No. 120 solvent oil, quinoline, kerosene; the mixing method is one or a combination of stirring, ultrasound, planetary ball milling, and the duration is 0.2~8h.
8. The method according to claim 1, characterized in that: In step (3), the method of solid-liquid separation of the precursor mixed liquid S5 is negative pressure rotary evaporation or spray granulation; the inert atmosphere in step (4) is nitrogen, argon or a mixed atmosphere of nitrogen and argon, and the sintering heating rate is 1~50℃ / min.
9. Use of the high-porosity silicon / carbon interpenetrating composite material according to claim 1 as a negative electrode material for lithium-ion secondary batteries.
10. The use according to claim 9, characterized in that: The high-porosity silicon / carbon interpenetrating composite material is used alone as an active material, mixed with a binder and a conductive agent, and coated on a copper foil as a negative electrode of a lithium-ion battery; or it is mixed with graphite in a certain proportion as a mixed active material, and then mixed with a binder and a conductive agent and coated on a copper foil as a negative electrode of a lithium-ion battery.
Citation Information
Patent Citations
Hierarchical porous silicon carbon composite structure taking diatomite as raw material and preparation method of hierarchical porous silicon carbon composite structure
CN108735992A
Electrode material with cross-linked carbon-coating mesoporous silicon particles and preparation method thereof
CN110289402A
High-tap-density porous silicon-carbon composite material, preparation method thereof and application of high-tap-density porous silicon-carbon composite material to negative electrode of lithium ion battery
CN113178552A
High-tap-density double-carbon-layer silicon-carbon composite material and preparation method thereof
CN113193183A
Preparation method of carbon-coated porous silicon negative electrode material for lithium ion battery
CN116826000A
Cited By
Modified silicon-carbon negative electrode material based on non-carbon-based porous skeleton and preparation method and application thereof
CN121416444A
